The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0233965
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of non-communicable diseases in people 50 years of age and older receiving HIV care in Latin America

Abstract: ¶ Membership of the Caribbean, Central and South American network for HIV epidemiology (CCASAnet) is provided in the Acknowledgments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
0
5
1
3
Order By: Relevance
“…In our study, although the rate of MSM was lower in the older group than the younger group, it remained the most common route of HIV in this group and was much higher than that found in a cross-sectional study in Taiwan (49.0%) [26] and a cohort study in Latin America (24%) [27]. However, the populations in those two studied were PLWH who had followup HIV care at a hospital, which may account for the difference.…”
Section: Discussioncontrasting
confidence: 74%
“…In our study, although the rate of MSM was lower in the older group than the younger group, it remained the most common route of HIV in this group and was much higher than that found in a cross-sectional study in Taiwan (49.0%) [26] and a cohort study in Latin America (24%) [27]. However, the populations in those two studied were PLWH who had followup HIV care at a hospital, which may account for the difference.…”
Section: Discussioncontrasting
confidence: 74%
“…The WHO 1 report of 2021 indicates that more than 15 million persons between the ages of 30–69 years die from an NCD every year; 85% of these ‘premature’ deaths take place in low- and middle-income nations. Again, Belaunzaran-Zamudio et al 23 found that between 2000 and 2015, multi-morbidity increased from 30% to 40% and the annual prevalence of NCDs among people aged 50 years or older living with HIV rose from 32% to 68%.…”
Section: Discussionmentioning
confidence: 99%
“…2 Some of the factors that increase susceptibility to human immunodeficiency virus (HIV) are also relevant for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus that causes COVID-19. 3,4 Certain comorbidities were stronger drivers of COVID-19 outcomes and were associated with an increased risk of death. 5 Opportunistic infections (OIs) are a leading cause of mortality in patients with acquired immunodeficiency syndrome (AIDS).…”
Section: Introductionmentioning
confidence: 99%